Colloidal Dynamics of Freshly Formed Iron Oxides under the Influence of Silicic Acid. Issue 3 (1st May 2019) - Dam, Than T. N.; Hoang, Nhung T.; Nguyen, Anh T. N.; Nguyen, Huan X.; Nguyen, Phuong M.; Nguyen, Khai M.; Nguyen, Minh N.
Abstract : Silicic acid and soluble Fe are among the most abundant components in acid mine drainage. During the oxidation of Fe(II), the interaction between silicic acid and freshly formed Fe oxides might change the colloidal dynamics, altering surface charge properties. However, the effects of silicic acid on colloidal Fe oxides formed from acid mine drainage are not fully understood. In this work, we examined the colloidal dynamics of freshly formed Fe oxides in synthetic acid mine drainage (prepared from FeSO4 solution) under the effect of silicic acid as a function of changes in pH and ionic strength. The results demonstrate that through adsorption, silicic acid progressively slows oxidation and enhances the dispersion of freshly formed Fe oxides by shifting the surface charge toward more negative values. This effect was most prominent between pH 5 and 9. The current results demonstrate that silicic acid enhances the dispersion and transport of freshly formed Fe oxides and suggest that aggregation‐based techniques for the treatment of Fe‐rich drainage may require further consideration of this effect. Core Ideas: Silicic acid may occur at a significant concentration in Fe‐rich acid mine drainage. During the oxidation of Fe, silicic acid can react and modify the Fe oxide surface charge. By shifting the surface charge to lower levels, silicic acid can favor Fe oxide dispersion. Silicic acid can thus promote the transport of acid mine drainage‐derived Fe(III) oxides.